PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP RETURN ON ASSETS PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BEI PERIODE 2014 - 2018 - SINTA USWATUN HASANAH; IBROHIM .; DINA KHAIRUNA SIREGAR (LP2MTBM MAKARIOZ, 2020)
Manufacturing industry is one of the mainstay sector in Indonesia. However, in recent years the performance of Indonesiamanufacturing sector is experiencing slowdown. Implementation of Corporate Social Responsibility disclosure, managerialownership and institutional ownership will maintain the existence of the manufacturing company as it will impact thecompany's productivity so that it will impact the company's performance. This research was conducted to determine theinfluence of Corporate Social Responsibility disclosure, managerial ownership and institutional ownership towards Return OnAssets. This research uses a quantitative approach. This research sample amounted to 185 consisting of 37 companies.Statistical testing using multiple linear regression analyses with a significance rate of 5%. The results of the T CorporateSocial Responsibility test show that T counts 4.444 > T table 1.97316 so that hypotheses 1 is acceptable. Unlike themanagerial holdings that show the value of the Count T-1569 < t table 1.97316 and its institutional ownership with T count-1.302 < t table 1.97316 so that hypotheses 2 and 3 are rejected. The F test results indicate that the F count 8.335 > F table2.65 so that the 4 hypothesis was received.